2001
DOI: 10.1007/s003300101043
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral transpopliteal approach for treatment of complex SFA and iliac occlusions

Abstract: We present a successful case of percutaneous intentional extraluminal recanalization (PIER) of bilateral long superficial femoral artery (SFA) occlusions and a long iliac artery occlusion through ultrasound-guided retrograde popliteal artery punctures. To our knowledge, PIER of SFA occlusions via popliteal approach has been reported in only three cases, and subintimal recanalization of combined SFA and iliac occlusions has not been reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…In fact, in the present study, one case occurred in which the creation of a new reentry site proximal to the remote reentry site created by the traditional subintimal technique allowed the stent to be placed, overcoming the suboptimal subintimal balloon angioplasty. Some surgeons report using retrograde popliteal access (15) for subintimal recanalization or a "kissing catheter" or "wire pull-through" technique (16, 17), which requires two access sites (femoral and popliteal). After femoral access and catheter or guide wire advancement through the subintimal plane around the occlusion, the patient is placed in a prone position, and the popliteal artery is accessed.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in the present study, one case occurred in which the creation of a new reentry site proximal to the remote reentry site created by the traditional subintimal technique allowed the stent to be placed, overcoming the suboptimal subintimal balloon angioplasty. Some surgeons report using retrograde popliteal access (15) for subintimal recanalization or a "kissing catheter" or "wire pull-through" technique (16, 17), which requires two access sites (femoral and popliteal). After femoral access and catheter or guide wire advancement through the subintimal plane around the occlusion, the patient is placed in a prone position, and the popliteal artery is accessed.…”
Section: Discussionmentioning
confidence: 99%
“…Yilmaz et al [36] recommended routine use of ultrasound guidance during the puncture procedure which can help demonstrate the orientation of the popliteal artery and vein in order to exclude the risk of arteriovenous fistula formation and to exclude the presence of a popliteal artery aneurysm where puncture would be hazardous. Alternatively, the retrograde puncture can be performed under fluoroscopic guidance: following dye injection from the femoral access the vessel at the intended puncture site will be filled with contrast medium via collaterals.…”
Section: Retrograde Popliteal Artery Recanalization Of Femoral Arterymentioning
confidence: 99%
“…No puncture site hematoma or arteriovenous fistula was encountered. In 2005 Yilmaz et al [36] published a retrospective review of 174 consecutive patients with 247 iliofemoral lesions who underwent retrograde popliteal artery catheterization using the ultrasound guidance. Their technical success was 100% and no complications occurred.…”
Section: Retrograde Popliteal Artery Recanalization Of Femoral Arterymentioning
confidence: 99%
“…Several reports have suggested that the initial success rate is high, but long-term patency is poor in the endovascular therapy of the femoropopliteal artery occlusive disease [8][9][10]. In order to recanalize the CTO lesions in the femoropopliteal artery, several techniques such as the subintimal technique [11], the duplexguided technique [12], and the bidirectional subintimal angioplasty via a popliteal artery approach [13,14] have been developed. In the subintimal technique, a stiff 0.035-in.…”
Section: Discussionmentioning
confidence: 99%